Moonlight and the pearler's daughter - Pook, Lizzie (Simon & Schuster, 2022)
"Western Australia, 1886. After months at sea, a slow boat makes its passage from London to the shores of Bannin Bay. The sea is a shocking blue, and gulls float above battered mangrove jetties. From the deck, young Eliza Brightwell and her family eye their strange new home. Here is an unforgiving land where fortune sits patiently at the bottom of the ocean. A land where pearl shells bloom to the size of soup plates. Where men are coaxed into unthinkable places and unspeakable acts by the promise of unimaginable riches. Ten years later, the pearl-diving boat captained by Eliza's eccentric father returns after months at sea--without Eliza's father on it. Whispers from the townsfolk point to mutiny or murder. Headstrong Eliza knows it is up to her to discover who, or what, is really responsible. As she searches for the truth, delving beneath the glamorous veneer of south sea pearls, Eliza discovers that, underneath it all, lies a town of sweltering, stinking decay. The sun-scorched streets of Bannin Bay, a place she once thought she knew so well, are teeming with corruption, prejudice and blackmail. How far is Eliza willing to push herself in order to solve the mystery and save the ones she loves? And what family secrets will come to haunt her along the way?"--